2001
DOI: 10.1128/aem.67.9.4358-4360.2001
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Malachite Green by the FungusCunninghamella elegans

Abstract: The filamentous fungus Cunninghamella elegans ATCC 36112 metabolized the triphenylmethane dye malachite green with a first-order rate constant of 0.029 mol h ؊1 (mg of cells) ؊1 . Malachite green was enzymatically reduced to leucomalachite green and also converted to N-demethylated and N-oxidized metabolites, including primary and secondary arylamines. Inhibition studies suggested that the cytochrome P450 system mediated both the reduction and the N-demethylation reactions.Malachite green, an N-methylated diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(155 citation statements)
references
References 25 publications
6
141
0
5
Order By: Relevance
“…To our knowledge, the P. putida CBB5 methylxanthine Ndm provides the first concrete example of a Rieske non-haem iron oxygenase with broadbased N-demethylase activity on a number of purine alkaloids. N-Demethylation (or N-dealkylation) reactions in eukaryotes and prokaryotes are known to be catalysed only by cytochrome P450s (Abel et al, 2003;Asha & Vidyavathi, 2009;Caubet et al, 2004;Cha et al, 2001;Guengerich, 2001;Tassaneeyakul et al, 1994), various flavo-enzymes (Chang et al, 2007;Kvalnes-Krick & Jorns, 1986;Meskys et al, 2001;Nishiya & Imanaka, 1993;Phillips et al, 1998;Shi et al, 2004;Wagner, 1982) and a ketoglutarate-dependent non-haem iron oxygenase (Tsukada et al, 2006). This study therefore broadens our understanding of the possible enzymic mechanism for N-demethylation and will aid the discovery of new microbial N-demethylases in the future.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, the P. putida CBB5 methylxanthine Ndm provides the first concrete example of a Rieske non-haem iron oxygenase with broadbased N-demethylase activity on a number of purine alkaloids. N-Demethylation (or N-dealkylation) reactions in eukaryotes and prokaryotes are known to be catalysed only by cytochrome P450s (Abel et al, 2003;Asha & Vidyavathi, 2009;Caubet et al, 2004;Cha et al, 2001;Guengerich, 2001;Tassaneeyakul et al, 1994), various flavo-enzymes (Chang et al, 2007;Kvalnes-Krick & Jorns, 1986;Meskys et al, 2001;Nishiya & Imanaka, 1993;Phillips et al, 1998;Shi et al, 2004;Wagner, 1982) and a ketoglutarate-dependent non-haem iron oxygenase (Tsukada et al, 2006). This study therefore broadens our understanding of the possible enzymic mechanism for N-demethylation and will aid the discovery of new microbial N-demethylases in the future.…”
Section: Discussionmentioning
confidence: 98%
“…The use of MG in fish farming is prohibited in the United States and the European Union (EU) due to its toxicological and potentially carcinogenic nature (Culp and Beland, 1996;Srivastava et al, 2004). However, MG is often illegally used by the fish farming industry due to its low cost, easy availability, and high efficacy against fungus, bacteria and parasite (Cha et al, 2001). Findings of MG residues in aquaculture products have frequently been reported in Rapid Alert System for Food and Feed (RASFF) notifications of the European Commission.…”
Section: Introductionmentioning
confidence: 99%
“…The UV λ max of the metabolites were within a narrow range with that of vincamine which indicates that their extinction coefficient at 270nm was not significantly different from that of the parent drug. Cha reported that the fungi Cunninghamella elegans was able to N-demethylate malachite green, where the metabolites showed a slight decrease (618 to 608nm) in absorption maxima (visible λ max ) than the substrate malachite green [12].…”
Section: Discussionmentioning
confidence: 99%